2007
DOI: 10.1186/1465-9921-8-57
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pulmonary antibodies with induced sputum and bronchoalveolar lavage induced by nasal vaccination against Pseudomonas aeruginosa: a clinical phase I/II study

Abstract: The nasal OprF-OprI-vaccine induces a lasting antibody response at both, systemic and airway mucosal site. IS is a feasible method to non-invasively assess bronchial antibodies. A further optimization of the vaccination schedule is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…The addition of OprF 190-342 -OprI 21-83 (FI) has the potential to protect immunized hosts against P. aeruginosa infection (Baumann et al 2007;Sorichter et al 2009). However, to date, mannose-modified chitosan microspheres have not been tested as an FI subunit vaccine delivery system candidate for immunization against P. aeruginosa infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of OprF 190-342 -OprI 21-83 (FI) has the potential to protect immunized hosts against P. aeruginosa infection (Baumann et al 2007;Sorichter et al 2009). However, to date, mannose-modified chitosan microspheres have not been tested as an FI subunit vaccine delivery system candidate for immunization against P. aeruginosa infection.…”
Section: Introductionmentioning
confidence: 99%
“…Only the outer membrane proteins (OPRs) have been effective as components of vaccines that exhibit immunological crossreactions between different serotypes Mansouri et al 2003;Mansouri et al 1999). A highly conserved recombinant fusion protein consisting of outer membrane proteins F ) and I (OprI 21-83 ) had non-toxic side effects and induced specific antibodies in human trials (Baumann et al 2007;Gocke et al 2003;Knapp et al 1999;Larbig et al 2001;Mansouri et al 2003;Sorichter et al 2009). Because of the mucosal colonization of P. aeruginosa, mucosal immunization results in enhanced mucosal immunity and may be superior to other routes of immunization (Hansen and Lehr 2012;Johansen 1996;Six et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…141 The levels of mucosal P. aeruginosa-specific IgA or IgG antibodies were similar with both immunization schedules 141 and were detected up to 1 y following immunization. 142 Even as the systemic boost induced higher serum IgG antibodies, nasal boost induced a longer-lasting mucosal IgA and IgG response against P. aeruginosa. 142 A subsequent phase I/II clinical trial in patients with chronic pulmonary disease demonstrated that nasal OprF-OprI vaccination followed by systemic boost was well tolerated and induced airway mucosal P. aeruginosa-specific IgG and IgA up to 6 mo in more than 90% of the vaccinees.…”
Section: Outer Membrane Proteinsmentioning
confidence: 99%
“…142 Even as the systemic boost induced higher serum IgG antibodies, nasal boost induced a longer-lasting mucosal IgA and IgG response against P. aeruginosa. 142 A subsequent phase I/II clinical trial in patients with chronic pulmonary disease demonstrated that nasal OprF-OprI vaccination followed by systemic boost was well tolerated and induced airway mucosal P. aeruginosa-specific IgG and IgA up to 6 mo in more than 90% of the vaccinees. 143 An Opr vaccine (CFC-101), composed of Opr extracts from four P. aeruginosa strains, induced Opr-specific antibody titer with opsonophagocytic activity and increased P. aeruginosa protection.…”
Section: Outer Membrane Proteinsmentioning
confidence: 99%
“…Klinische Phase-II-und -IIIImpfstudien hierzu sind z. T. bereits abgeschlossen bzw. in Planung [20,21].…”
Section: Zystische Fibroseunclassified